Improving Social Studies Learning Outcomes through Communicative Efforts using the Means-End Analysis Model in Online Learning for Grade V Students at Inpres Bangkala III Elementary School in Makassar City - Nurwahidah; Nurhadifah Amaliyah; R. Supardi (Jurnal Mercusuar, 2022)
Improving Social Studies Learning Outcomes Through the Means-End Analysis Model Based on Online Learning for Fifth Grade Students at SD Inpres Bangkala III, Makassar City. Supervised by Nurhadifah Amaliyah and R. Supardi. This study aims to enhance social studies learning outcomes using the Means-End Analysis communication model in the fifth grade of SD Inpres Bangkala III, Makassar City. The approach used is quantitative, employing classroom action research (CAR) consisting of two cycles, each comprising three sessions involving planning, implementation, observation, testing, and documentation activities. The research subjects consist of 26 students. This can be observed through the learning outcomes of students in Cycle I and Cycle II. Out of 26 students, 15 students fell into the category of not meeting the passing criteria, accounting for 58%, while 11 students, making up 42%, achieved passing scores. The average score in Cycle I was 63.33%. In Cycle II, there were 5 students (19%) who did not meet the passing criteria, and 21 students (81%) who did, resulting in an average score of 81.42%. Thus, there was an evident improvement in students’ learning outcomes from Cycle I to Cycle II. The conclusion drawn from this study is that the application of the Means-End Analysis learning model can enhance students’ learning outcomes in the fifth grade at SD Inpres Bangkala III, Makassar City.